The role of competitve advantage in strategic determinants of export perfomance: Theoretical framework - Orlando Lima Rua; Alexandra Silva França (The International Journal of Management Science and Information Technology (IJMSIT), 2015)
The main goal of this article is to analyze the role that competitive advantage takes on the relationship between entrepreneurial orientation, resources and capabilities, and export performance of Portuguese small and medium enterprises exporting footwear industry. Additionally this research has the following specific objectives: 1) to propose and test a model to analyze the relationship between these determinants, competitive advantage and export performance, and 2) to analyze how the competitive advantage influences the adoption of certain internationalization's strategies. In this context, we performed a literature review of the thematic object of analysis, later we carry out a quantitative, descriptive and exploratory empirical study. Thus, in view of the scope of the proposed objectives, the methodological approach will be based on the adoption of quantitative methodology for the development of this work.
Keywords: 650; entrepreneurial orientation; resources and capabilities; competitive advantage; export performance